Kontekstualisasi dan Pembumian Fikih Berbasis Realitas Ke-Indonesiaan: Perspektif Hazairin dan Munawir Sjadzali - Tarmizi, Tarmizi; Salenda, Kasjim; HL, Rahmatiah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The concept of Indonesian fiqh is an idea that is characteristic of the implementation of Islamic law in Indonesia which is in accordance with the character and nuances of Indonesian society. The emergence of the concept of Indonesian fiqh cannot be separated from the ideas of important figures who contributed ideas to Islamic law in Indonesia. This research is library research carried out by collecting and reviewing various literature related to the concept of Indonesian fiqh which was initiated by several important figures and their ideas. The data analysis technique uses qualitative descriptive analysis through analysis of the thoughts of influential figures in grounding Indonesian fiqh. The results of the research show that Hazairin's thoughts on Indonesian fiqh gave birth to the concept of the Indonesian school of thought or the Syafi'i plus Indonesia school which was projected by including Islamic law in the national legal system. Then Munawir Syadzali with the concept of humanitarian ijtihad through the positivization of Islamic law. Several of the proposals and methodologies that have been initiated have the same ideals, namely wanting a new fiqh format that is in accordance with social realities in Indonesia.